THE PRICE OF ONE SWEET CALORIE - Sebastien Buttet; Veronika Dolar (International Journal of Food and Agricultural Economics, 2015)
We propose a new measure for food prices to further examine the impact of changes in food prices and real income on individuals’ eating decisions and weight. We calculate price per calorie for food consumed away from home and food consumed at home as the dollar amount spent by households on each food category divided by the number of calories consumed. We use our newly constructed time series for price per calorie as an input into a neoclassical model of eating decisions and weight. Our goal is to propose a quantitative explanation for the increase in calories consumed away from home as well as changes in weight for men and women 1971 and 2006. We find that prices determine the allocation of calories across food types, while income determines the total number of calories consumed and thus individuals' weight. Based on our results, we share the view that taxes on food will impact what people eat but will have limited effect on reducing the population body-mass index or the obesity prevalence